Comparison of Shunt Types in the Norwood Procedure for Single-Ventricle Lesions - Ohye, Richard G; Sleeper, Lynn A; Mahony, Lynn; Newburger, Jane W; Pearson, Gail D; Lu, Minmin; Goldberg, Caren S; Tabbutt, Sarah; Frommelt, Peter C; Ghanayem, Nancy S; Laussen, Peter C; Rhodes, John F; et al. (The New England journal of medicine, 2010)
Hypoplastic left heart syndrome is a complex congenital heart lesion that requires a three-stage procedure for surgical palliation. This clinical trial examines two approaches to the first stage of the procedure, and the results provide important guidance for the most appropriate surgical management of this serious lesion. This clinical trial examines two approaches to the first stage of the Norwood procedure, and the results provide important guidance for the most appropriate surgical management of this serious lesion. Hypoplastic left heart syndrome and related anomalies involving a single right ventricle are characterized by hypoplasia of the left heart and the aorta, with compromised systemic cardiac output (Figure 1). Infants with the syndrome generally undergo a three-stage reconstruction culminating in the Fontan procedure. The first operation (stage I) is the Norwood procedure, in which the right ventricle is connected to a reconstructed aorta with the use of the proximal main pulmonary artery for systemic outflow. Pulmonary blood flow is reestablished by means of a shunt from the pulmonary artery to the systemic circulation. In the second operation (stage II), . . .